2018
DOI: 10.7717/peerj.5360
|View full text |Cite
|
Sign up to set email alerts
|

Mate availability does not influence mating strategies in males of the sexually cannibalistic spiderArgiope bruennichi

Abstract: BackgroundSexual selection theory predicts that male investment in a current female should be a function of female density and male competition. While many studies have focused on male competition, the impact of female density on male mating investment has been widely neglected. Here, we aimed to close this gap and tested effects of mate density on male mating decisions in the orb-web spider Argiope bruennichi. Males of this species mutilate their genitalia during copulation, which reduces sperm competition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 106 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…We selected the wasp spider Argiope bruennichi, which features a wasp-like banding pattern that may have evolved as a tool to lure prey [37]. This species is used as a model organism for the investigation of sexual dimorphism, chemical ecology, reproductive behavior, microbiome analysis and range expansion linked to climate change [38][39][40][41][42][43][44][45][46][47]. Its venom has been extracted for bioactivity assays but has not been analyzed in detail [27].…”
Section: Introductionmentioning
confidence: 99%
“…We selected the wasp spider Argiope bruennichi, which features a wasp-like banding pattern that may have evolved as a tool to lure prey [37]. This species is used as a model organism for the investigation of sexual dimorphism, chemical ecology, reproductive behavior, microbiome analysis and range expansion linked to climate change [38][39][40][41][42][43][44][45][46][47]. Its venom has been extracted for bioactivity assays but has not been analyzed in detail [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that males rather use a threshold rule than a best-of-n strategy [51,53,54]. Under best-of-n strategy, males should either sample several females before they mate or they should immediately visit the largest female, if they are able to distinguish females of different body size via chemical cues.…”
Section: Introductionmentioning
confidence: 99%
“…Under best-of-n strategy, males should either sample several females before they mate or they should immediately visit the largest female, if they are able to distinguish females of different body size via chemical cues. However, in several previous studies, males showed neither of these mate searching patterns [51,54]. In contrast, males adjusted their mating strategy (monogyny, bigyny) to female body size even though no alternative The test frames were custom-made and allowed for stationing females on fixed positions within the arena.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected the wasp spider Argiope bruennichi, which features a wasp-like banding pattern that may have evolved as a mimetic warning trait (Bush et al, 2008) This species is used as a model organism for the investigation of sexual dimorphism, chemical ecology, reproductive behavior, microbiome analysis and range expansion linked to climate change (e.g. Chinta et al, 2010;Welke and Schneider, 2010;Zimmer et al, 2012;Wilder and Schneider, 2017;Cory and Schneider, 2018;Ganske and Uhl, 2018;Sheffer et al, 2019;Krehenwinkel and Tautz, 2013;Krehenwinkel and Pekar, 2015;. Its venom has been extracted for bioactivity assays but has not been analyzed in detail (Friedel and Nentwig, 1989).…”
Section: Introductionmentioning
confidence: 99%